Performance Expentancy, Effort Expentancy, Social Influence on Behavioral To Use Through Behavioral Intention in Using Mobile Banking in Malang (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Performance Expentancy, Effort Expentancy, Social Influence on Behavioral To Use Through Behavioral Intention in Using Mobile Banking in Malang Currently, information technology in all lines of business is very fast, as is the use of existing technology in the banking sector, namely by implementing digital banking services. Digital banking services by all banks are considered very highly in the world of banking in the world and Indonesia. Mobile Banking is also the right answer to the needs of people who will make transactions quickly. This is in accordance with the initial objective of implementing a secure Mobile Banking system aimed at providing smooth and easy banking by utilizing information technology. Research to examine the extent to which Performance Expectancy, Effort Expectancy, Social Influence, and Behavioral Intention affect Behavioral Usage. This research is an explanatory research, the location of this research is conducted in Malang, East Java. The population in this study were all people who transact using Mobile Banking with a sample size of 135 respondents. Data analysis techniques used descriptive statistical analysis, path analysis and hypothesis testing. From the results of the analysis and discussion, it is found that the results of Performance Expectancy, Effort Expectancy, Social Influence have a significant effect on Bahavioral Intention, furthermore, Performance Expectancy, Effort Expectancy, have a significant effect on Behavioral ToUsage while Social Influence has no significant effect on Behavioral ToUsage. The indirect effect is obtained from the results of Performance Expectancy, Effort Expectancy has a significant effect on Behavioral to Usage through Bahavioral Intention, except for the Social Influence variable.